Earn more through onion seed production - Verma, K. S.; Kushwah, S. S.; Singh, P. P.; Baghel, B. S. (Indian Horticulture, 2019)
Malwa region is potential area of onion production. Therefore to fulfill the onion seed requirement of farmers, it becomes imperative to make the quality seed of onion available to farmers locally at cheaper rates. This could be possible with good quality onion seed production by farmers themselves through adopting suitable technologies. The planting of onion bulbs from 1 to 15 October along with application of 5 tonnes FYM + 100 kg N, 60kg P2 O5 + 90 kg K2 O/ha + biofertilizer in Malwa plateau results in higher onion seed yield and income.